2019
DOI: 10.1155/2019/1341370
|View full text |Cite
|
Sign up to set email alerts
|

An Inulin-Specific Lectin with Anti-HIV-1 Reverse Transcriptase, Antiproliferative, and Mitogenic Activities from the Edible Mushroom Agaricus bitorquis

Abstract: A novel lectin (ABL) was purified from the dried fruiting bodies of Agaricus bitorquis. An efficient 3-step purification protocol involved two consecutive steps of ion exchange chromatography on Q-Sepharose and SP-Sepharose and gel filtration by FPLC on Superdex 75. ABL is a monomeric protein with the molecular mass of 27.6 kDa, which is different from other lectins from genus Agaricus. Its N-terminal amino acid sequence is EYTISIRVYQTNPKGFNRPV which is unique and sharing considerably high similarity of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…semotus lectin (ASL) exhibited a non-specific agglutination towards the human ABO erythrocytes, characteristics mainly associated with an unique group of promiscuous lectins (panalectins), which have been identified mainly in plants, but rarely in mushrooms (Kuku et al 2000;Akinyoola et al 2016;Oladokun et al 2019). However, lectins have been already identified and isolated within the genus Agaricus, there is not any previous report on the lectins of A. semotus (Kawagishi et al 1988;Mikiashvili et al 2006;Nakamura-Tsuruta et al 2006;Zhang et al 2019).…”
Section: Purifi Cation Hemagglutinating Activity and Sugar Specifi City Of Agaricus Semotus Lectin (Asl)mentioning
confidence: 99%
“…semotus lectin (ASL) exhibited a non-specific agglutination towards the human ABO erythrocytes, characteristics mainly associated with an unique group of promiscuous lectins (panalectins), which have been identified mainly in plants, but rarely in mushrooms (Kuku et al 2000;Akinyoola et al 2016;Oladokun et al 2019). However, lectins have been already identified and isolated within the genus Agaricus, there is not any previous report on the lectins of A. semotus (Kawagishi et al 1988;Mikiashvili et al 2006;Nakamura-Tsuruta et al 2006;Zhang et al 2019).…”
Section: Purifi Cation Hemagglutinating Activity and Sugar Specifi City Of Agaricus Semotus Lectin (Asl)mentioning
confidence: 99%
“…Furthermore, lectins from mushrooms can act as immunomodulators by activating Tlymphocyte or stimulating dendrites or cytokines, as in Table 2. 52 Nowadays, the transport of Ca 2+ by SARS-CoV has been documented to activate inflammasome stimulation. It has been proposed that the cytokine is related to infected patients by SARS-CoV-2.…”
Section: Fungal Lectinsmentioning
confidence: 99%
“…This suggested that POL is a monomeric protein composed of one subunit. In a close study carried out by Zhang et al (2019) Agaricus bitorquis lectin was found to be a monomeric protein with a molecular mass of 27.6 kDa. Mushroom lectins isolated from different mushroom species vary in molecular masses, subunit number and carbohydrate specificity (Yang et al 2009).…”
Section: Characterization Of Lectin From P Ostreatus Ss89mentioning
confidence: 99%
“…A few lectins are multimeric such as the novel hexameric lectin isolated from Ganoderma lucidum with a molecular weight of 114-kDa. To date, a lectin from Pholiota squarrosa possesses the lowest molecular mass of 4.5 kDa (Zhang et al, 2019). (6.5, 16, 30, 37, 52, 66, 95, 130, 175 and 270).…”
Section: Characterization Of Lectin From P Ostreatus Ss89mentioning
confidence: 99%
See 1 more Smart Citation